Analysis of mediator’s influence on economic efficiency of dispute and conflict resolution - A. A. Barzov; A. V. Vlasov; M. V. Vetlinskaya (Путеводитель предпринимателя, 2021)
Mediation as an alternative method of conflict resolution has increasingly become the subject of numerous studies. Due to its interdisciplinary nature, mediation can be viewed from the perspective of different sciences. This article analyzes the economic component of the mediator’s role as a key figure in the negotiation process and offers a phenomenological model of economic risks in dispute resolution with his participation.